The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.12957/epp.2016.33447
|View full text |Cite
|
Sign up to set email alerts
|

A anorexia na clínica contemporânea: considerações sobre o sintoma

Abstract: Este artigo aborda a especificidade do sintoma na psicanálise a partir da análise de um caso clínico sobre anorexia. Delimitam-se aspectos do caso que retratam a clínica do mal-estar contemporâneo a partir dos seguintes temas-eixo: anorexia e adolescência; recusa alimentar; a relação com o pai; e, psicanálise e medicina. Levando-se em consideração tais aspectos, destaca-se a anorexia como sintoma analítico a depender da constituição de uma demanda de análise e da relação transferencial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 3 publications
1
2
0
Order By: Relevance
“…The fathers of that study showed a preference for more solitary practices. This finding is also supported by the study by Santos and Zanotti (2016), which portrays the absence of the father in the patient's family life and proves that this distancing has a relationship with the psychopathological symptoms.…”
Section: Resultssupporting
confidence: 65%
See 2 more Smart Citations
“…The fathers of that study showed a preference for more solitary practices. This finding is also supported by the study by Santos and Zanotti (2016), which portrays the absence of the father in the patient's family life and proves that this distancing has a relationship with the psychopathological symptoms.…”
Section: Resultssupporting
confidence: 65%
“…However, three studies are coauthored by American researchers, in collaboration with authors from Australia, Canada and Israel, so that the country has participation in four of the 23 articles analyzed, followed by Spain (three), Israel (two), Poland (two), Austria, China and Turkey, with one study each. Finally, Brazil is the only South American country included in the list of country of origin of publications, with one study (Santos & Zanotti, 2016).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation